2019
DOI: 10.1097/01.nep.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Veterans as Students in Higher Education: A Scoping Review

Abstract: AIM The aim of this study was to determine what is known about military veterans as students in higher education and inform nurse educators. BACKGROUND Military veterans are increasingly enrolling in higher education and in nursing programs and may provide a recruitment source for nursing education. METHOD A scoping review of literature published after 2011 was performed to determine characteristics of milit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Nonetheless, Veterans working toward a college degree continue to experience difficulties fitting in. Dyar (2019) reported that Veterans struggle to adapt from a structured military environment to a more permissive campus life. It seems important to note that the study population consisted of student-clinicians working toward a degree and licensure in Nursing, hardly low intensity, high-spontaneity, or permissive programs.…”
Section: Vocational/financial Difficulties Experienced By Veteransmentioning
confidence: 99%
“…Nonetheless, Veterans working toward a college degree continue to experience difficulties fitting in. Dyar (2019) reported that Veterans struggle to adapt from a structured military environment to a more permissive campus life. It seems important to note that the study population consisted of student-clinicians working toward a degree and licensure in Nursing, hardly low intensity, high-spontaneity, or permissive programs.…”
Section: Vocational/financial Difficulties Experienced By Veteransmentioning
confidence: 99%
“…There are two more recently published scoping reviews. Dyar (2019) focused on describing the characteristics of student veterans through the lens of their suitability for nursing degrees. Based on 12 papers (published 2008-2018), Dyar outlined the strengths of student veterans (e.g., sense of duty) as well as their barriers to academic success (e.g., personal struggles).…”
Section: Existing Reviewsmentioning
confidence: 99%
“…Ghosh et al grouped 24 papers (published 2009Ghosh et al grouped 24 papers (published -2018 into four themes: mental health, academic and career development, support, and identity. Although both Dyar (2019) and Ghosh et al (2019) assessed veterans' mental and physical health more holistically than Barry et al (2014) and Borsari et al (2017), all four reviews are limited by the scope of included studies, which focused on the challenges facing veterans more than veterans' strengths. Similarly, these existing reviews provide a limited picture of academic outcomes, partly due to few journal articles quantitatively investigating academic outcomes.…”
Section: Existing Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…SV are at a higher risk of mental health disruptions due to the complex health needs associated with their time in the service, often because of traumatic injuries (Hinkson et al, 2021;Hoffmire et al, 2023). According to Dyar (2019), complex health needs in veterans can be defined as a combination of physical and psychological conditions such as PTSD, anxiety, depression, insomnia, alcohol or substance misuse, and suicidal thoughts or attempts. Despite psychological conditions being so prevalent in this population, it may be difficult for SV to seek help related to mental health, and faculty may overlook the consequences due to the rigors of the academic environment (Hinkson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%